2014
DOI: 10.5999/aps.2014.41.3.218
|View full text |Cite
|
Sign up to set email alerts
|

Research Priorities in Light of Current Trends in Microsurgical Training: Revalidation, Simulation, Cross-Training, and Standardisation

Abstract: Plastic surgery training worldwide has seen a thorough restructuring over the past decade, with the introduction of formal training curricula and work-based assessment tools. Part of this process has been the introduction of revalidation and a greater use of simulation in training delivery. Simulation is an increasingly important tool for educators because it provides a way to reduce risks to both trainees and patients, whilst facilitating improved technical proficiency. Current microsurgery training intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…It seems very important to cite a study published by Gawande, where he reported significantly important data regarding errors in surgery, considering that 53% occur due to inexperience or lack of competence in the area, 43% occur due to lack of communication and 33 % of these errors are attributed to fatigue and high workload [25]. For this reason, we consider it an essential requirement to acquire adequate training in MS, so that professionals are prepared before putting it into practice and thus minimize any risk of error when acting.…”
Section: Discussionmentioning
confidence: 99%
“…It seems very important to cite a study published by Gawande, where he reported significantly important data regarding errors in surgery, considering that 53% occur due to inexperience or lack of competence in the area, 43% occur due to lack of communication and 33 % of these errors are attributed to fatigue and high workload [25]. For this reason, we consider it an essential requirement to acquire adequate training in MS, so that professionals are prepared before putting it into practice and thus minimize any risk of error when acting.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] These scores display the added advantage of construct validation, allowing the reproducible demonstration of progress and competency-based assessments in revalidation, or work-based assessments. 2,8 The translation of simulated experience to patient clinical outcomes has not yet been undertaken in microsurgical simulation 13 but this would provide the ultimate proficiency benchmark.…”
Section: Discussionmentioning
confidence: 99%
“…traditional high intensity, high cost, high fidelity courses are being augmented by local practice facilities in individual departments, and trainees are being encouraged to practice outside the operating room (OR). 6,8 Third, the increasing ethical drive to replace, refine, and reduce the use of living animals in microsurgical simulation training, [9][10][11] highlights our responsibility to optimize non-living options.…”
mentioning
confidence: 99%
“…These time restrictions are increasing the need for simula-tion experiences outside of the operating room to expedite progress on the steep microsurgical learning curve. 13,14,[16][17][18][19][20][21][22] As such, we propose a new microsurgical model that provides a realistic microsurgical simulation of the DIEP free flap breast reconstruction with real-time respiratory excursion simulating the deep thoracic cavity. The aim of this study was threefold: to delineate realistic intraoperative measurements, to describe the simulation model based on these measures, and to conduct a pilot study evaluating the simulator as an educational resource.…”
mentioning
confidence: 99%